การสร้างรูปแบบการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษา สำหรับครูระดับมัธยมศึกษา: Constructing the Evaluation Learning Management Model Based on STEM Education Approach for High School Teachers - Nattapon Yotha ณัฐพล โยธา; Songsak Phusee-orn ทรงศักดิ์ ภูสีอ่อน (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
การวิจัยครั้งนี้มีความมุ่งหมายเพื่อ 1) ศึกษาสภาพปัจจุบัน ปัญหาและความต้องการจำเป็นในการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาสำหรับครูระดับมัธยมศึกษา 2) สร้างรูปแบบการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาสำหรับครูระดับมัธยมศึกษา ซึ่งการวิจัยครั้งนี้ผู้วิจัยได้ดำเนินการวิจัย 2 ระยะ คือ ระยะที่ 1 ศึกษาสภาพปัจจุบัน ปัญหาและความต้องการจำเป็นในการประเมินฯ กลุ่มเป้าหมาย ได้แก่ ผู้เชี่ยวชาญ จำนวน 7 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์แบบกึ่งโครงสร้าง วิเคราะห์ข้อมูลโดยการสังเคราะห์เอกสารและการวิเคราะห์เนื้อหา ระยะที่ 2 การสร้างรูปแบบการประเมินฯ กลุ่มเป้าหมาย ได้แก่ ผู้เชี่ยวชาญ จำนวน 12 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แบบประเมินความเหมาะสมและความเป็นไปได้ของร่างรูปแบบการประเมินฯ 2) แบบประเมินคู่มือการประเมินฯ วิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหาในส่วนที่เป็นข้อมูลเชิงคุณภาพและส่วนที่เป็นข้อมูลเชิงปริมาณวิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. ผลการศึกษาสภาพปัจจุบัน ปัญหาและความต้องการจำเป็นในการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาสำหรับครูระดับมัธยมศึกษาพบว่า 1) ปัจจุบันการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษายังไม่มีการติดตามประเมินการจัดการเรียนการสอนของครูและไม่มีแนวทางการประเมินที่ชัดเจน 2) ปัญหาของการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาพบว่าครูไม่มีรูปแบบในการประเมินการจัดการเรียนรู้ 3) มีความต้องการรูปแบบการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาที่มีความชัดเจน มีขั้นตอนในการประเมินที่เป็นระบบ เหมาะสมและมีความเป็นไปได้ในการนำไปใช้ประเมินในสถานการณ์จริง 2. รูปแบบการประเมินการจัดการเรียนรู้ตามแนวทางสะเต็มศึกษาสำหรับครูระดับมัธยมศึกษาประกอบด้วย 6 องค์ประกอบ คือ 1) ความมุ่งหมายการประเมิน 2) สิ่งที่มุ่งประเมิน 3) วิธีการประเมิน 4) แหล่งผู้ประเมิน 5) เกณฑ์การประเมิน และ 6) การสะท้อนผลการประเมิน The purposes of the current study were 1) to investigate the current situation, problems, and needs for constructing an evaluation learning management model based on the STEM Education approach for high school teachers and 2) to construct an evaluation learning management model based on the STEM Education approach for high school teachers. The study was divided into 2 phases: Phase 1 was the investigation of the current situation, problems, and needs for constructing the model. The targets were 7 experts. The instrument was a semi-interview form. The data were analyzed by document analysis and content analysis. Phase 2 was the development of an evaluation learning management model. The targets were 12 experts. The instruments were 1) an evaluation form with the appropriateness and feasibility of the model and 2) an evaluation form for the evaluation learning management model manual. The data were analyzed by content analysis, arithmetic mean, and standard deviation. The results of the study were as follows. 1. In terms of the current situation, problems, and needs for constructing an evaluation learning management model based on the STEM Education approach for high school teachers, 1) it could be noted that high schools lack systematic management of STEM Education evaluation, 2) teachers have failed to apply evaluation of STEM Education. Most teachers evaluated the assignments and projects, and 3) clear procedures of STEM Education were needed. Moreover, systematization, convenience, feasibility, were recommended by the participants to develop a model that is effective in developing teachers’ evaluation ability. 2. An evaluation learning management model based on the STEM Education approach for high school teachers includes 6 components which are 1) purposes of the evaluation, 2) expected outcomes, 3) evaluation methods, 4) evaluators, 5) criteria, and 6) evaluation reflection.